Outcomes of patients with systemic sclerosis-associated polyarthritis and myopathy treated with tocilizumab or abatacept: a EUSTAR observational study. Issue 7 (19th December 2012) - Elhai, Muriel; Meunier, Marine; Matucci-Cerinic, Marco; Maurer, Britta; Riemekasten, Gabriela; Leturcq, Tifenn; Pellerito, Raffaele; Von Mühlen, Carlos Alberto; Vacca, Alessandra; Airo, Paolo; Bartoli, Francesca; Fiori, Ginevra; et al.
Abstract : Objective: To evaluate the safety and effectiveness of tocilizumab and abatacept in systemic sclerosis (SSc)-polyarthritis or SSc-myopathy. Methods: 20 patients with SSc with refractory polyarthritis and seven with refractory myopathy from the EUSTAR (EULAR Scleroderma Trials and Research) network were included: 15 patients received tocilizumab and 12 patients abatacept. All patients with SSc-myopathy received abatacept. Clinical and biological assessments were made at the start of treatment and at the last infusion. Results: After 5 months, tocilizumab induced a significant improvement in the 28-joint count Disease Activity Score and its components, with 10/15 patients achieving a EULAR good response. Treatment was stopped in two patients because of inefficacy. After 11 months' treatment of patients with abatacept, joint parameters improved significantly, with 6/11 patients fulfilling EULAR good-response criteria. Abatacept did not improve muscle outcome measures in SSc-myopathy. No significant change was seen for skin or lung fibrosis in the different groups. Both treatments were well tolerated. Conclusions: In this observational study, tocilizumab and abatacept appeared to be safe and effective on joints, in patients with refractory SSc. No trend for any change of fibrotic lesions was seen but this may relate to the exposure time and inclusion criteria. Larger studies with longer follow-up are warranted to further determine the safety and effectiveness of these drugs in SSc.